My phone is not your phone / Norhayati Rafida Abdul Rahim, Muhammad Nizam Awang@Ali and Norailis Ab. Wahab. - Abdul Rahim, Norhayati Rafida; Awang@Ali, Muhammad Nizam; Ab. Wahab, Norailis (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
In this advanced era of communication technology, users connect across time and place. In the organization, mobile phones, smartphones, tablets, notebooks, and personal computers have become very important, allowing people to share and access documents easily and fast. This article is written based on the management case study approach that exhibits a multi-national company, Mondelez Malaysia Sales Sdn. Bhd. The company is a part of the Mondelēz International group of companies. Mondelēz International brings the brand that offers quality, convenience, and truly delicious taste to consumers worldwide. One of the brands is Cadbury chocolate. In 2014, Mondelez experienced social media's negative aspects concerning an anonymous report on porcine DNA, which is found on its two batches of Cadbury chocolate. Mondelez's reputation suffered, and it lost approximately RM36 Million within ten days. Later, the announcement is made by the Ministry of Health that the Cadbury chocolate is Halal and safe from any non-halal substance. This case study wishes to identify 1) the impact of social media, 2) the crisis management by Mondelez, and 3) the impacts on the reputation that the department of corporate communication has to deal with. This case study suggests that there should embody efficiency, sensitivity, the psychology of communication, emotions, and ethics of communication. Simultaneously, the stakeholders, corporate governance, and standard operating procedures must be in place.